The Influence of the Problem-Based Learning Model Assisted by PhET Simulations on Students' Problem-Solving Abilities and Mastery of Physics Concepts - Liana, Liana; Kosim, Kosim; Taufik, Muhammad (Balai Publikasi Indonesia, 2023)
This study aims to examine the effect of problem-based learning model assisted by PhET simulations on problem solving ability and mastery of physics concepts of students. This type of research is Quasi Experimental with non-equivalent control group design. The population of this study were all students of class XI IPA SMAN 4 Mataram with sampling technique using purposive sampling technique, because there were four classes XI IPA, so it was determined that class XI IPA 1 as the experimental class and class XI IPA 2 as the control class. Based on the results of the study, the average value of physics problem solving ability of students in the experimental class was 45.09, while the average value of problem-solving ability of the control class was 39.61, while the average value of concept mastery of the experimental class was 70 and the control class was 51.15. Data on problem solving ability and concept mastery of both classes are normally distributed and both are homogeneous. Data on problem solving ability and concept mastery were analyzed using the polled variance t-test at a significant level of 5% and obtained of problem solving ability of 2.24, while concept mastery obtained of 6.18 and obtained of 2.00, with hypothesis testing criteria if is greater than then is rejected and is accepted. Based on the results of this study, it shows that there is an effect of problem-based learning model assisted by PhET simulations on problem solving ability and mastery of physics concepts of students.